Adynamic bowel syndrome. Report of a case with disturbance of the cholinergic innervation. Issue 9 (September 1977) - Puri, P; Lake, B D; Nixon, H H
Abstract : A case of adynamic bowel syndrome is described. Full thickness biopsies of the large bowel showed the presence of ganglion cells, no acetylcholinesterase positive nerves in the lamina propria, submucosa or among the smooth muscle cells of the circular and longitudinal muscle coats, and absence of the argyrophil plexus. Electron microscopic examination showed replacement of the normal axon bundle by vacuolated tracts with small round bodies in one area--probably viral. Neuronal cytoplasm also showed similar vacuolation. It is suggested that the damage to the cholinergic innervation may be caused by a neurotoxic agent.